Gut-brain communication: Functional anatomy of vagal afferents - Berthoud, Hans Rudolf; Münzberg, Heike; Morrison, Christopher D.; Neuhuber, Winfried (Current Opinion in Neurobiology, 2025)
There is increasing interest in interoceptive mechanisms as a key player in mental health. The vagus nerve is an important pathway of communication between the body and the brain, and recent advances in neurobiological techniques have enabled the identification of function-specific populations of vagal sensory neurons. Here we briefly review this progress, focusing on vagal innervation of the gut and its involvement in ingestive behavior, metabolic regulation, and immune defense. While we have learned much about the organization of the peripheral interface of the sensory vagal system, dissemination of information within the brain is still poorly understood. Yet, a deeper understanding of the brain's integration of vagal input will be necessary for the informed development of neuromodulation therapies for various diseases linked to interoception.
CRIS-Team Scopus Importer:2025-06-06